Transference of strength and power adaptation to sports performance - Horizontal and vertical force production - Randell, A. D.; Cronin, J. B.; Keogh, J. W. L.; Gill, N. D. (Strength and Conditioning Journal, 2010)
The training of horizontal propulsive force generation is one aspect of many sports that is not easily simulated with traditional gym-based resistance training methods, which principally work the leg musculature in a vertical direction. Given that most motion involves an integration of both vertical and horizontal force production, transference of gym-based strength gains may be improved if exercises were used that involved both vertical and horizontal force production.